Induction and Its Relevance to the Transformation of Sharia Economic Law in Indonesia: A Study of Four Madhhabs - Enang Hidayat (Universitas Islam Sultan Agung, 2023)
This research aims to determine the existence and urgency of induction in the methodology of Islamic law of the four schools of jurisprudence and its relevance to the transformation of Sharia economic law in Indonesia. This study falls under the category of normative Islamic legal research using a conceptual and philosophical approach. Primary data is sourced from the foundational books of Islamic jurisprudence of the four schools: